Type I IFN – A blunt spear in fighting HIV-1 infection. Issue 2 (April 2015) - Acchioni, Chiara; Marsili, Giulia; Perrotti, Edvige; Remoli, Anna Lisa; Sgarbanti, Marco; Battistini, Angela
Highlights HIV-1 components can effectively trigger an innate immune response through various Pattern Recognition Receptors. IFN is produced early during HIV-1 infection, but this initial response is dampened by viral escape mechanisms. Immune clearance is prevented and the virus replicates and spreads, while establishing a persistent infection. Prolonged and sustained stimulation of IFN during the chronic phase of infection drives chronic immune activation and inflammation. Chronic immune activation and inflammation contribute to the immunopathogenesis of progressive HIV-1 disease.